Teacher's Pedagogical Competence in Implementing of Kurikulum Merdeka Belajar (Independent Learning Curriculum) in Elementary School - Ayu Reza Ningrum; Nurul Hidayah; Ayu Cahya Utami; Nur Hidayah; Rifda Elfiah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The aim of the research is to determine the pedagogical competence of teachers in Kurikulum Merdeka Belajar (independent learning curriculum) at Assalam Elementary School of Bandar Lampung. The research method used is qualitative descriptive research. The subject in this research is lower class teachers totaling 12 teachers. Data collection techniques use interviews and observation. Data analysis techniques in research apply three stages, namely data reduction, data display, and drawing conclusion. The research results display that the pedagogical competence of teachers at Assalam Islamic Elementary School is running well and optimally. There are 5 of the 6 indicators of pedagogical competence in the reasonable category. These indicators include the ability to master student characteristics, master learning theory and educational learning principle, organize educational learning, facilitate the development of student potential, effective communication, and be empathetic towards students. Meanwhile, the indicator of mastering the evaluation of learning outcomes is in the quite good category. In this way, the pedagogical competencies possessed by teachers can be a pioneer of change in realizing the goals of the Kurikulum Merdeka Belajar. Therefore, mastery of pedagogical competencies which is capable and adaptive is able to navigate the flexibility offered by the independent curriculum and create student-centered learning that is delightful and meaningful.